Advice from Experience: Communicating Incomplete Information Incompletely. (30th June 2014) - Benjamin, Daniel; Budescu, David V.
ABSTRACT People utilize advice often with limited knowledge of their advisers' expertise. We examine the effects of learning mode on giving and receiving advice in two separate but linked studies. Advisers learned about a choice between two lotteries from either description or experience before writing advice. The decision makers only read this advice before choosing between the options. Advisers who learned from description provided better summarized information more confidently and were ultimately preferred by the decision makers. Advisers who learned from experience were more risk averse and tended to describe their experiences signaling their informational deficiency. Decision makers were sensitive to the subtle differences between the two cases, even when not informed of their adviser's learning mode. We discuss the implications of the adviser's learning mode within the context of various decision environments and the risk‐uncertainty continuum. Advisers perform under risk when learning from description compared with performing under uncertainty when learning from experience. Copyright © 2014 John Wiley & Sons, Ltd.